Surveiller les femmes incarcérées en maison centrale. La construction d’une différenciation de la surveillance pénitentiaire au XIXe siècle - Amélie Imbert; Anne Jennequin (Criminocorpus)
This article challenges the androcentric perspective that has historically and currently dominated representations of prisons, focusing on the issue of the surveillance of female prisoners in the 19th century. In France, during the July Monarchy, a prison policy aimed at segregating inmates by sex established the principle that female convicts in central detention and correctional facilities should be supervised by individuals of the same sex. The Sisters’ Service Regulations of 22 May 1841 helped to achieve this, by establishing the involvement of specific staff, namely nuns. These regulations contributed to the creation of a specific organisation for women's prisons, reconfiguring the function of surveillance by distinguishing it from that performed by guards in men’s prisons. This article sheds light on the specific nature of the role assigned to these nuns, highlighting that the conditions for a special 'prison education' for female prisoners were established on religious grounds. The introduction of differentiated prison supervision for men and women had a lasting impact on the organisation of penal institutions and their staffing.